1990
DOI: 10.1111/j.1346-8138.1990.tb01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Case of Mycosis Fungoides and One of Parapsoriasis en Plaque with Topical PUVA Using a Monofunctional Furocoumarin Derivative, 4,6,4'‐Trimethylangelicin

Abstract: A case of plaque stage mycosis fungoides and one of parapsoriasis en plaque were treated with topical PUVA therapy using a monofunctional furocoumarin derivative, 4,6,4'-trimethylangelicin (TMA). Both patients showed complete clearance of eruptions within 16 treatments. The therapeutic effectiveness of TMA was confirmed by the fact that those eruptions exposed to UVA alone, without TMA application, showed slower and less significant improvement. Histologically, dermal infiltrates of mycosis cells and associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…SPP may be treated with emollients, topical tar preparations, topical corticosteroids and/or PUVA therapy. Response to therapy is variable 1–7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPP may be treated with emollients, topical tar preparations, topical corticosteroids and/or PUVA therapy. Response to therapy is variable 1–7 …”
Section: Discussionmentioning
confidence: 99%
“…Classification of these disorders is controversial and the current generally accepted classification includes three entities: large‐plaque parapsoriasis (LPP), small‐plaque parapsoriasis (SPP) and pityriasis lichenoides 1 . Treatment of LPP, SPP and mycosis fungoides (MF) for many years have consisted of broadband UVB (BB‐UVB) phototherapy 2 as well as psoralen‐UVA therapy (PUVA) 3–9 . Although about 10–30% of cases of LPP result in early form MF, the relation of SPP with MF is still a matter of discussion 10–13 .…”
Section: Introductionmentioning
confidence: 99%
“…The MA and MTA under study (see Scheme 1) were synthesized as in previous works (5,6). The solvents benzene (Baker, UV grade), cyclohexane (Fluka, UV grade), 1,4-dioxane (Aldrich, 99+%) and ethanol (Carlo Erba, RS grade) were used as received, while acetonitrile (Carlo Erba, RPE) was purified by distillation over P,O, before use.…”
Section: Methodsmentioning
confidence: 99%
“…The incapacity to photoinduce these lesions in macromolecules, in vitro and in vivo, explains the lower genotoxicity of angelicins. For this reason, they have been used in the treatment of hyperproliferative skin diseases (psoriasis), as well as for mycosis fungoides (4,5).…”
mentioning
confidence: 99%
“…In microorganisms and mammalian cells TMA shows a high antiproliferative effect and reduced genotoxicity in comparison with 8-MOP (20). In limited clinical studies (20)(21)(22) using topically applied TMA and UVA, it was demonstrated that it had therapeutic activity.…”
Section: Discussionmentioning
confidence: 99%